Tujuan dan Manajemen Pendidikan dalam Perspektif K.H. Ahmad Dahlan - Diningrum Citraningsih (Saliha, 2021)
The purpose of this study was to determine the study of education in the perspective of K.H. Ahmad Dahlan as a Muhammadiyah figure, the focus of research on the idea of ​​educational goals and management of educational institutions. The research method used is library research with a descriptive-qualitative approach, data sources from books, journal articles, and other relevant sources. Data collection techniques used are documentation techniques and data analysis techniques in the form of content analysis. The results of the first research are educational goals in the perspective of K.H. Ahmad Dahlan's mission is to form human beings who are pious in religious knowledge, broad-minded, with general knowledge, ready to fight and serve for the advancement of Islam. Second, make changes in education management which include the opening of learning rights for all communities, educational curriculum, education administration system, leadership roles and behavior or ethics of members of educational institutions.